Copper-streptocycline application modulates pomegranate (Punica granatum L.) secondary metabolism and antioxidant pathways against Xanthomonas axonopodis pv. punicae-induced bacterial blight - Mustafa, Ghulam; Rajwana, Ishtiaq A.; Faried, Hafiz Nazar; Naqvi, Syed Atif Hasan; Khalil, Uzman; Iqbal, Muhammad Umer; Al-Ansari, Mysoon M.; Elshikh, Mohamed S.; Manghwar, Hakim; Liu, Fen (Frontiers in Plant Science, 2025)
IntroductionBacterial blight of pomegranate (Punica granatum L.), caused by Xanthomonas axonopodis pv. punicae (Xap), is a major constraint to pomegranate production and fruit quality. Effective management strategies are essential to mitigate yield losses and orchard decline.MethodsField experiments were conducted over three consecutive seasons to evaluate the efficacy of six bactericides applied at 15-day intervals (April–July) on three pomegranate cultivars such that, Sindhuri, Kalehar, and Sava using a randomized complete block design. Treatments included copper oxychloride (3000 ppm) combined with streptocycline (500 ppm) (T7) alongside other bactericides. Disease incidence, severity, marketable yield, fruit weight, aril quality, and biochemical parameters were recorded and statistically analyzed.ResultsThe T7 treatment proved most effective, significantly reducing bacterial blight intensity. In the Sindhuri cultivar, mean disease incidence was lowest on leaves (3.51%), fruits (3.88%), twigs (0.58%), and trees (3.59%). Disease severity values were similarly minimized, with the highest mean disease reduction observed on leaves (77.63%), fruits (79.76%), twigs (76.10%), and whole trees (76.90%). T7 also improved productivity, with marketable yield (89.60 kg), fruit weight (245 g), and hundred-aril weight (43.30 g), while enhancing biochemical traits such as TSS (17.90 °Brix), vitamin C (36.50 mg/100 mL), antioxidants (86.40% inhibition), and enzymatic activities (CAT: 21.30 U/mg protein; POD: 1.35 U/mg protein).DiscussionAmong the cultivars, Sindhuri displayed the highest resistance, followed by Kalehar and Sava. The copper-streptocycline combination not only suppressed bacterial blight but also enhanced fruit yield, quality, and biochemical composition. These findings demonstrate the potential of optimized bactericide application in sustaining pomegranate productivity and reducing orchard losses due to Xap.